Seasonal upwelling drives surface water biogeochemistry with implication for ocean acidification along the Northwest African coast - Jamal, Chaimaa; Makaoui, Ahmed; Chierici, Melissa; Cervantes, David; Chair, Adil; Hammou, Hasnaa Nait; Idrissi, Mohammed; Bouthir, Fatima Zohra; Ettahiri, Omar; Yousfi, Samia; Bouamrani, Mouna Latifa (Frontiers in Marine Science, 2025)
This study assesses the impact of intensified upwelling on the marine carbonate system along the Northwest African coast, from Cape Blanc (21°N) to Cape Cantin (33°N), a region where ocean acidification observations remain limited. We analyze surface water variability using data from two oceanographic surveys conducted aboard the R/V Dr. Fridtjof Nansen in spring and autumn 2022. The analysis is based on observational data of temperature, salinity, dissolved oxygen, chlorophyll a, pH, total alkalinity, and derived carbonate system variables. In spring, upwelling was widespread across the study area, while in autumn it was more localized near Cape Draa (28°30'N), between Cape Boujdour and Dakhla (25°30N–23°30N), and at Cape Blanc (21°N). Both spring and autumn were influenced by low-oxygenated South Atlantic Central Water (SACW), which is rich in DIC (2160–2250 µmol/kg), and upwelled to the surface, lowering pH (~7.85–7.95) and aragonite saturation state (ΩAr ~1.5–2.5). The strongest acidification signals were observed in autumn at Cape Draa (28°30N) and Cape Blanc (21°N), where the lowest pH (7.8) and ΩAr (1.5), along with the highest DIC (2250 µmol/kg), were recorded. The study clearly shows that the lowest pH values and highest DIC concentrations were related to the influence of SACW upwelling at Cape Blanc. It was also evident that areas with high chlorophyll a coincided with higher ΩAr and pH in spring. This suggests that primary production (PP) during spring counteracts the effect of upwelled low-pH water along the coast. Areas of high PP, such as at Cape Draa (28°30N), experienced increased DIC levels and enhanced acidification after the bloom season, potentially influenced by organic matter remineralization. Our findings highlight the influence of upwelling and biological processes on surface carbonate chemistry along the Northwest African coast. This study emphasizes the necessity of long-term monitoring to assess ocean acidification trends and their ecological implications in this vulnerable region.